2011
DOI: 10.1111/j.1875-595x.2011.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial to assess maintenance of gingival health by a novel gel to foam dentifrice containing 0.1%w/w o-cymen-5-ol, 0.6%w/w zinc chloride

Abstract: A randomised clinical trial to assess maintenance of gingival health by a novel gel to foam dentifrice containing 0.1%w⁄w o-cymen-5-ol, 0.6%w⁄w zinc chloride Objectives: To assess the ability of 0.1%w ⁄ w o-cymen-5-ol ⁄ 0.6%w ⁄ w zinc chloride gel to foam dentifrice to maintain gingival health compared to a sodium fluoride control dentifrice. Design: Following a baseline examination, subjects went through a regimen to bring them to a high level of gingival health. This involved a professional dental prophylaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Dental plaque plays a major role in the aetiology of periodontal disease. The mainstay of preventing periodontal disease is the control of plaque and thus the prevention of plaque induced gingivitis (1). …”
Section: Introductionmentioning
confidence: 99%
“…Dental plaque plays a major role in the aetiology of periodontal disease. The mainstay of preventing periodontal disease is the control of plaque and thus the prevention of plaque induced gingivitis (1). …”
Section: Introductionmentioning
confidence: 99%
“…The level of agreement between the initial and repeat MGI was calculated using a Kappa coefficient. The intra‐examiner kappa scores were 0.96 (95% CI 0.95, 0.96) for Study I 3 and 0.95 (95%CI 0.94, 0.96) for Study II 4 . These two results demonstrate excellent 8 repeatability and consistency of the examiners scoring.…”
Section: Discussionmentioning
confidence: 60%
“…Zinc products have been evaluated for plaque control, but also focused on halitosis control [35-39; [42]. Some products have demonstrated some efficacy on plaque [43] and gingivitis [44,45]: a 12-week study reported a 20.7% reduction in plaque and 38.1% in gingivitis, of a 0.1% o-cymen-5-ol and 0.6% zinc chloride dentifrice, when compared to a control dentifrice (p < 0.0001) [44]; however, only one 6-month trial is available [45], demonstrating reductions of 25.3% in plaque and 18.8% in gingivitis, when compared to the placebo. In summary, when they are used as single ingredients, they have limited effects on plaque; but they may also be used in combination with other active agents (triclosan, CPC, CHX), which may improve substantivity and efficacy.…”
Section: Metal Salts: Zinc Saltsmentioning
confidence: 99%